The floral repressors TEMPRANILLO1 and 2 modulate salt tolerance by regulating hormonal components and photo‐protection in Arabidopsis - Osnato, Michela; Cereijo, Unai; Sala, Jan; Matías‐Hernández, Luis; Aguilar‐Jaramillo, Andrea E.; Rodríguez‐Goberna, María Rosa; Riechmann, José Luis; Rodríguez‐Concepción, Manuel; Pelaz, Soraya (The Plant journal : for cell and molecular biology, 2021)
SUMMARY Members of the plant specific RAV family of transcription factors regulate several developmental and physiological processes. In the model plant Arabidopsis thaliana, the RAV TEMPRANILLO 1 (TEM1) and TEM2 control important phase changes such as the juvenile to adult and the vegetative to reproductive transitions. Besides their known regulatory function in plant development, a transcriptomics analysis of transgenic plants overexpressing TEM1 also revealed overrepresentation of Gene Ontology (GO) categories related to abiotic stress responses. Therefore, to investigate the biological relevance of these TEM‐dependent transcriptomic changes and elucidate whether TEMs contribute to the modulation of plant growth in response to salinity, we analyzed the behavior of TEM gain and loss of function mutants subjected to mild and high salt stresses at different development stages. With respect to increasing salinity, TEM overexpressing plants were hypersensitive whereas the tem1 tem2 double mutants were more tolerant. Precisely, tem1 tem2 mutants germinated and flowered faster than the wild‐type plants under salt stress conditions. Also, tem1 tem2 plants showed a delay in salt‐induced leaf senescence, possibly as a consequence of downregulation of jasmonic acid biosynthesis genes. Besides a shorter life cycle and delayed senescence, tem1 tem2 mutants appeared to be better suited to withstand oxidative stress as they accumulated higher levels of α‐tocopherol (an important antioxidant metabolite) and displayed a slower degradation of photosynthetic pigments. Taken together, our studies suggest novel and crucial roles for TEM in adaptive growth as they modulate plant development in response to environmental changes such as increasing soil salinity. Significance Statement To withstand environmental stresses, as those caused by climate change, plants have evolved highly interconnected pathways to trigger stress responses that regulate key developmental and physiological processes, because survival requires rapid adaptation to a changing environment. Our studies suggest novel and crucial roles for TEM in adaptive growth since they modulate plant development in response to environmental changes, such as increasing soil salinity, by regulating senescence and hormonal and photo‐protective mechanisms.